Development of Tea Seed Oil Nanostructured Lipid Carriers and In Vitro Studies on Their Applications in Inducing Human Hair Growth - Pornthida Riangjanapatee; Mattaka Khongkow; Alongkot Treetong; Onuma Unger; Chutikorn Phungbun; Supatchaya Jaemsai; Chatchaya Bootsiri; Siriporn Okonogi (MDPI AG, 2022)
Synthetic drugs used to treat hair loss cause many side-effects. Natural tea seed oil possesses many activities that can suppress hair loss. However, it is oily and sticky in direct application. In this study, tea seed oil loaded nanostructured lipid carriers (NLC) using Tween 80 (NLC-T), Varisoft 442 (NLC-V), and a combination of both surfactants (NLC-C) was developed. The obtained nanoformulations showed spherical particles in the size range 130-430 nm. Particle size and size distribution of NLC-C and NLC-T after storage at 4, 25, and 40 °C for 90 days were unchanged, indicating their excellent stability. The pH of NLC-T, NLC-V, and NLC-C throughout 90 days remained at 3, 4, and 3.7, respectively. NLC-C showed significantly greater nontoxicity and growth-stimulating effect on human follicle dermal papilla (HFDP) cells than the intact oil. NLC-T and NLC-V could not stimulate cell growth and showed high cytotoxicity. NLC-C showed melting point at 52 ± 0.02 °C and its entrapment efficiency was 96.26 ± 2.26%. The prepared hair serum containing NLC-C showed better spreading throughout the formulation than that containing the intact oil. Using 5% NLC-C showed a 78.8% reduction in firmness of the hair serum while enhancing diffusion efficiency by reducing shear forces up to 81.4%. In conclusion, the developed NLC-C of tea seed oil is an effective alternative in stimulating hair growth. Hair serum containing NLC-C obviously reduces sticky, oily, and greasy feeling after use.